1999
DOI: 10.1016/s1387-6473(99)00075-5
|View full text |Cite
|
Sign up to set email alerts
|

The youngest lobe-dominated radio sources

Abstract: We present an analysis of multi-epoch global VLBI observations of the Compact Symmetric Objects: 2352+495 and 0710+439 at 5 GHz. Analysis of data spread over almost two decades shows strong evidence for an increase in separation of the outer components of both sources at a rate of ∼ 0.2h −1 c (for q • =0.5 and H • = 100h kms −1 Mpc −1 ). Dividing the overall sizes of the sources by their separation rates implies that these Compact Symmetric Objects have a kinematic age ≪ 10 4 years. These results (and those fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
240
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(254 citation statements)
references
References 14 publications
13
240
1
Order By: Relevance
“…The first results from this analysis of the 5 GHz VLBI data were published in , and Owsianik et al (1999). In June 2000 we have performed new VLBA+Effelsberg 5 GHz observations of these sources, thereby extending the time baseline to more than twenty years.…”
Section: Introductionmentioning
confidence: 99%
“…The first results from this analysis of the 5 GHz VLBI data were published in , and Owsianik et al (1999). In June 2000 we have performed new VLBA+Effelsberg 5 GHz observations of these sources, thereby extending the time baseline to more than twenty years.…”
Section: Introductionmentioning
confidence: 99%
“…consistent with those derived by multiple epoch presented here and elsewhere conclude the census of observations at 6 cm by Owsianik & Conway CSOs in the complete PR and CJ1 sample. There are (1998), Owsianik et al (1998) and Owsianik et al 15 confirmed CSOs in this 200 source sample, (these proceedings) and will not be discussed further.…”
Section: Polarization Chapter 2 Css Gps and Hfpmentioning
confidence: 76%
“…Light blu symbols represent the data taken in U band, the red symbols are observation taken in C band. Square and circles are relative to the observations used in this work, the diamonds are relative to the work by Owsianik et al (1998) and the triangles represent the observations from the paper by Taylor et al, (2000). The 5 GHz observations were compared with the work by Owsianik et al, (1998).…”
Section: Multi-epoch Observations Chapter 5 Discussionmentioning
confidence: 99%
See 2 more Smart Citations